Mirror Neuron in the Perspective of Islamic Education - Fadilah Husni; Suyadi (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2020)
This article serves to determine the effect of social intelligence in various ways. In particular, mirror neurons in the perspective of Islamic education. Mirror neurons are mirror brains. The point of the mirror brain is the brain's ability to imitate in several ways, either imitating what is felt or imitating what is seen. The working principle of the mirror brain is that it will work to imitate something optimally if it is done with habituation or done continuously. In addition, mirror neurons play a role in the healing process of the sick, for example stroke sufferers can recover with mirror neuron system therapy, because the brain in stroke sufferers will be trained how to adapt to potential exercises, so that patients can restore the flexibility of joints that cannot be moved. . In this study, it is used in the literature method, and mirror neurons are divided into several discussions, namely characteristics, and social intelligence